2004
DOI: 10.1016/j.jvs.2003.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of secondary interventions after abdominal aortic aneurysm endovascular repair

Abstract: With close follow-up and a significant number of secondary operations, this 8-year experience has not included any aneurysm ruptures to date. Secondary operations did not lead to increased mortality, but were associated with more surgical conversions and with a higher clinical failure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 28 publications
5
91
0
2
Order By: Relevance
“…Previous studies have also described this problem (13). Excessive oversizing of the graft may lead to infolding of the graft material within the graft lumen (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also described this problem (13). Excessive oversizing of the graft may lead to infolding of the graft material within the graft lumen (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Furthermore, the development of devices, expansion of indications, and improved clinical results with regard to EVR are anticipated. Particularly in the case of thoracic aortic diseases, EVR offers the theoretical advantage of being minimally invasive compared with conventional open surgery under cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The initial and midterm results for repair using these handmade SGs for thoracic and abdominal aortic diseases in high-risk patients are considered to be satisfactory. [3][4][5][6][7][8][9][10][11][24][25][26][27][28][29][30] However, endoleaks were the reason for poor initial results, whereas the reason for poor midterm results was migration. Furthermore, all endoleaks and migrations occurred during our early phase of surgeries using flexible SGs that were designed on the basis of a concept identical to the commercially available SGs wherein 1 device can be used to treat various aortic contours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reintervention is often required at a rate that is higher than that of OSR. 103 In fact, Becquemin et al 9 found that 27% of patients who underwent EVAR required a secondary procedure (mean follow-up was 28 months). Another issue is that hospital and physician times are required post-operatively to insure the integrity of the stent graft.…”
Section: Eurostar Registrymentioning
confidence: 99%